Detection of Cystoisospora belli among Children in Sulaimaniyah, Iraq - Ali, Fatimah Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Cystoisospora belli inhabits epithelial cells of the upper part of human small intestine, producing resistant oocysts that are infrequently detected in stool specimens but can spread and cause infection. Objectives: To determine the rate of C. belli infection among children and correlate the rate of infection with the patient's variables. Patients and Methods: In this cross-sectional study, 156 fresh stool samples were collected from children suffering from diarrhea or abdominal discomfort in Dr Jamal Ahmed Rashid Pediatric Teaching Hospital, Sulaimaniyah, Iraq, from July to August 2021. Slides for direct wet mount and fixed smears stained with modified ZiehlNeelson stain were prepared for each sample. Additionally, the correlation between the parasitic infection rate and patients' variables (age, gender, residency, duration of infection, and type of drinking water/stool) was determined. Results: None examined stool samples were positive for C. belli oocyst by direct wet mount technique, while the modified ZN staining method revealed 42 (26.92%) positive samples. The highest rate of C. belli infection (15.38%) was found among children aged 4-6 years (p=0.000), male patients (15.38%), patients who lived in an urban area (23.08%) (p≥0.05), had infection for 1-3 days (15.38%) (p=0.038), used bottle water (15.38%) (p=0.02), and patients had liquid/semiliquid stool type (11.54%) (p=0.485). On the other hand, modified ZN stain showed coinfections with other protozoa, including Cryptosporidium spp., Microsporidia spp, Cyclospora spp. and Blastocystis hominins at rates of 10.26%, 5.13%, 3.85% and 1.28%, respectively. Conclusions: There was a relatively high rate of C. belli infection among children in Sulaimaniyah, Iraq, despite other types of protozoa
Keywords: Cystoisospora belli; coccidian parasite; children diarrhoea; cross sectional study